Turkish EFL learners’ perceptions of using ChatGPT vs. online dictionaries for English collocations - Berra Artul (Yayasan Mitra Persada Nusantara, 2026)
This study investigates Turkish EFL (English as a Foreign Language) learners’ perceptions, attitudes, and usage patterns regarding ChatGPT and online dictionaries for the acquisition of English collocations. Utilizing a quantitative research design, data were collected via an online questionnaire from 27 university-level participants, including preparatory and master’s students. The findings reveal that while online dictionaries remain the primary and most trusted resource for checking grammatical patterns and seeking reliable definitions (M=3.81), ChatGPT is increasingly perceived as a valuable